KORELASI ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Hamiza, Hamiza; Kresnadi, Hery; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research is to analyze correlation between motivation with students learning outcomes in the thematic learning class IV SDN 18 Sungai Kakap. The method is descriptive method, with the form the study of correlation. The population in this study is all students of SDN 18 Sungai Kakap, amounting to 251 students. The samples were 27 students who determined by purposive sampling technique, namely class IV. The results of this study indicate that learning motivation of 3 students has very good category (11,11%), 14 students with good category (51,58%), 10 students is good enough (37,04%) and the results learning odd UTS value is 21 (77,78%) students are complete and 6 (22,22%) students are not complete. The odd UAS value is 100% complete students. In statistical calculations using the correlation Product Moment obtained motivation with UTS learning oucomes greater have rcount than rtable (0,524>0,388) while correlation learning motivation with UAS learning outcomes is that having rcount is greater than rtable (0,559>0,388) in significant level 5%. Then Ha is accepted as the ?Medium? category. Then this calculation proves that there is a positive correlation between motivation with students learning outcomes in the thematic learning class IV SDN 18 Sungai Kakap.Keywords: Correlation, Learning Motivation, Learning Outcomes and Thematic Learning